Autophagy-Related ncRNAs in Pancreatic Cancer - Simone Donati; Cinzia Aurilia; Gaia Palmini; Irene Falsetti; Teresa Iantomasi; Maria Luisa Brandi (MDPI AG, 2022)
Pancreatic cancer (PC) is a malignancy accounting for only 3% of total cancers, but with a low 5-year relative survival rate. Approximately 80% of PC patients are diagnosed at a late stage when the disease has already spread from the primary site. Despite advances in PC treatment, there is an urgently needed for the identification of novel therapeutic strategies for PC, particularly for patients who cannot undergo classical surgery. Autophagy is an evolutionarily conserved process used by cells to adapt to metabolic stress via the degrading or recycling of damaged or unnecessary organelles and cellular components. This process is elevated in PC and, thus, it contributes to the onset, progression, and cancer cell resistance to chemotherapy in pancreatic tumors. Autophagy inhibition has been shown to lead to cancer regression and to increase the sensitivity of pancreatic cells to radiation and chemotherapy. Emerging studies have focused on the roles of non-coding RNAs (ncRNAs), such as miRNAs, long non-coding RNAs, and circular RNAs, in PC development and progression. Furthermore, ncRNAs have been reported as crucial regulators of many biological processes, including autophagy, suggesting that ncRNA-based autophagy targeting methods could be promising novel molecular approaches for specifically reducing autophagic flux, thus improving the management of PC patients. In this review, we briefly summarize the existing studies regarding the role and the regulatory mechanisms of autophagy-related ncRNAs in the context of this cancer.